THE DANGERS OF GADGET USE ON THE MENTAL HEALTH DEVELOPMENT OF ADOLESCENTS IN KEMURANG WETAN VILLAGE, TANJUNG DISTRICT, BREBES REGENCY, INDONESIA - M. Naufal Fadli Mubarok (NATARASA: Journal of Counseling and Psychology, 2026)
The rapid advancement of digital technology has significantly increased gadget use among adolescents, creating both educational opportunities and psychological challenges. Excessive and uncontrolled gadget use has become a growing concern due to its potential negative effects on adolescents' mental health, including anxiety, emotional instability, sleep disturbances, reduced social interaction, and symptoms of digital addiction. This study aims to analyze the dangers of gadget use on the mental health development of adolescents in Kemurang Wetan Village, Tanjung District, Brebes Regency, Indonesia. The research employed a qualitative case study approach involving adolescents, parents, community leaders, and educators as research participants selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the interactive model of data analysis consisting of data reduction, data display, and conclusion drawing. The findings indicate that excessive gadget use has negatively influenced adolescents' emotional, cognitive, and social development. Common problems identified include increased anxiety, irritability, decreased concentration, sleep disorders, social withdrawal, and dependence on online entertainment and social media. Limited parental supervision and low digital literacy further exacerbate these psychological risks. However, adolescents who received consistent parental guidance, participated in religious and community activities, and maintained balanced digital habits demonstrated better emotional regulation and healthier social relationships. The study concludes that preventing the adverse effects of gadget use on adolescent mental health requires collaborative efforts among families, schools, communities, and local government through digital literacy education, strengthened parental supervision, and the promotion of healthy digital behavior. These findings contribute to the development of community-based strategies for safeguarding adolescent mental health in the digital era.